Vapor Phosphorylation of Cellulose by Phosphorus Trichlo-Ride: Selective Phosphorylation of 6-Hydroxyl Function-The Synthesis of New Antimicrobial Cellulose 6-Phosphate(III)-Copper Complexes - Marcin H. Kudzin; Zdzisława Mrozińska; Paweł Urbaniak (MDPI AG, 2021)
This research is focused on a synthesis of copper-cellulose phosphates antimicrobial complexes. Vapor-phase phosphorylations of cellulose were achieved by exposing microcrystalline cellulose to phosphorus trichloride (PCl3) vapors. The cellulose-O-dichlorophosphines (Cell-O-PCl2) formed were hydrolyzed to cellulose-O-hydrogenphosphate (P(III)) (Cell-O-P(O)(H)(OH)), which, in turn, were converted into corresponding copper(II) complexes (Cell-O-P(O)(H)(OH)∙Cu2+). The analysis of the complexes Cell-O-P(O)(H)(OH)∙Cu2+ covered: scanning electron microscopy (SEM), attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), atomic absorption spectrometry with flame excitation (FAAS), and bioactivity tests against representative Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus). The antimicrobial tests of synthesized Cell-O-P(O)(H)(OH)∙Cu2+ revealed their potential applications as an antibacterial material.